Rethinking Dover: Religion, Science, and the Values of Democratic Citizenship - Liebell, Susan P. (Politics and religion, 2012)
The Dover decision restricted the mention of Intelligent Design in a public school science classroom yet the Dover opinion offers an inadequate defensive position. Liberal democracy can exclude Intelligent Design based on the Establishment Clause yet courts do not affirm the teaching of best available science or connect teaching science to other constitutional rights, duties, or institutions. Although Dover has triggered a debate over the role of religion in public and private life, the case reveals complex issues regarding science, citizenship, and the values of liberal democratic civic identity. In three sections, this article (1) reviews the creationism jurisprudence; (2) dissects the Dover decision; and (3) suggests an alternative juridical approach grounded in an education case, Plyler v. Doe, in which education creates citizens who are politically competent, economically fit, and capable of self-development. The conclusion reframes the debate over Intelligent Design as one of civic identity and political reproduction arguing that liberals, using the ideas of Brennan, Marshall, and Breyer must make a positive case for the role of science in shaping the liberal citizen, worker, and person.